Epidemiological Characteristics of Tuberculosis and Treatment Outcome from 2019 to 2023 in Gandaki Province of Nepal - Yadav, Rajesh Kumar; Baral, Sushila; Khadka, Khim Bahadur; Mishra , Man Mohan; Shah, Naveen Prakash; Adhikari, Ramesh Prasad; Dhakal, Roshan; Poudel, Purna Chadra; Basaula , Laxman; Paudel, Srijana; et al. (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2025)
Introduction: Tuberculosis is a one of the major public health problem globally which with rank in top ten diseases and a significant public health problem in Nepal as well as global and it continues to pose a serious threat to the health of the population and development of the country. This study aimed to assess epidemiological characteristics of tuberculosis patients and their treatment outcomes in Gandaki Province. Methods: A retrospective descriptive epidemiological study was conducted in the Gandaki Province of Nepal. The data were obtained from the Health Management Information System (HMIS) and the eTB system of Gandaki Province of Nepal from 2019 to 2023. Patient information from 11,532 individuals was screened, with incomplete or incorrect data excluded from the analysis. The analysis was conducted using SPSS version 22 and QGIS version 3.38.1 to understand the epidemiology of tuberculosis in the area over the past five years. Results: From 2019 to 2023, a total of 11,532 tuberculosis patients were reviewed in Gandaki Province, showing an increasing trend in annual TB cases. Kaski and Nawalparasi East districts reported the highest cumulative numbers, with 2,999 cases (26.01%) and 2,536 cases (21.99%) respectively. About 62.79% of the patients were male, with the most affected age group being 15 to 55 years. Nearly three-fourths of the cases were pulmonary TB. The proportion of HIV-positive TB patients increased from 0.90% in 2019 to 2.11% in 2023. March to June was peak months for TB notifications. The number of death and treatment failure cases was gradually increasing over the period. The proportion of re-treatment cases of TB had increased over the period from 1.64% in 2019 to 3.48% in 2023. In the same period, there was increasing trend in proportion of DR TB cases i.e. 10.65% to 18.69% by 2023. Conclusion: This study highlights the increasing trend of tuberculosis cases in Gandaki Province, with over one-third diagnosed at private health facilities. A significant number of cases were reported between March and June and more than one per cent of TB patients being HIV-positive. The trend of re-treatment and drug resistant TB cases has risen from 2019 to 2023. Strengthening active case finding in rural areas, among the elderly and vulnerable groups is essential. The National TB program should effectively implement the DOTS strategy for medication adherence and adopt a public-private mix approach for early TB diagnosis.